THE DIASPORA FEATURES OF AMERICAN-BORN INDONESIANS IN UNITED STATES OF AMERICA - Nabilla, Noor Vatha (Annual International Conferences on Language, Literature, and Media; No 1: 3rd AICOLLIM (Annual International Conference on Language, Literature, and Media)DO - 10.18860/aicollim.v2i1.1351, 2021)
Language phenomena can be triggered by some factors such as diaspora. Diaspora is the dispersion of ethnic groups that move to other countries for particular purposes but still have collective memories about their homeland and attempt to recreate their socio-economic, political, and cultural institutions as a form of minority survival in the host land. This study investigates the daily activities done by American-Born Indonesian in the USA related to diaspora phenomena while they lived in the USA and after they moved to Indonesia. The data were taken from interview by video call and recording audio. Additional data such as text messages were also used as supporting data. The data were analyzed by using diaspora features theory proposed by Cohen (2008) and reasons and impacts classification by Zhao (2015). The result indicates that the participants show some of their features as diaspora and the reasons and impacts of not speaking Indonesian while in the USA. The result also provides their language solution when they moved to Indonesian since they could not speak Indonesian or Javanese fluently.